Prevalence of IgG and Neutralizing Antibodies against Staphylococcus aureus Alpha-Toxin in Healthy Human Subjects and Diverse Patient Populations - Wu, Yuling; Liu, Xu; Akhgar, Ahmad; Li, Jia J.; Mok, Hoyin; Sellman, Bret R.; Yu, Li; Roskos, Lorin K.; Esser, Mark T.; Ruzin, Alexey (Infection and immunity, 2018)
Staphylococcus aureus causes an array of serious infections resulting in high morbidity and mortality worldwide. This study evaluated naturally occurring serum anti-alpha-toxin (anti-AT) antibody levels in human subjects from various age groups, individuals with S. aureus dialysis and surgical-site infections, and S. aureus -colonized versus noncolonized subjects. Anti-AT immunoglobulin G (IgG) and neutralizing antibody (NAb) levels in infants (aged ≤1 year) were significantly lower than those in other populations. In comparison to adolescent, adult, and elderly populations, young children (aged 2 to 10 years) had equivalent anti-AT IgG levels but significantly lower anti-AT NAb levels. Therefore, the development of anti-AT NAbs appears to occur later than that of AT-specific IgG, suggesting a maturation of the immune response to AT. Anti-AT IgG levels were slightly higher in S. aureus -colonized subjects than in noncolonized subjects. The methicillin susceptibility status of colonizing isolates had no effect on anti-AT antibody levels in S. aureus -colonized subjects. The highest anti-AT IgG and NAb levels were observed in dialysis patients with acute S. aureus infection. Anti-AT IgG and NAb levels were well correlated in subjects aged >10 years, regardless of colonization or infection status. These data demonstrate that AT elicits a robust IgG humoral response in infants and young children that becomes stable prior to adolescence, matures into higher levels of NAbs in healthy adolescents, and becomes elevated during S. aureus infection. These findings may assist in identifying subjects and patient populations that could benefit from vaccination or immunoprophylaxis with anti-AT monoclonal antibodies.